Immunogenicity of inactivated coronavirus disease 2019 vaccines in patients with chronic hepatitis B undergoing antiviral therapy - Wang, Wen-Xin; Jia, Rui; Song, Jin-Wen; Zhang, Xiaoning; Zhou, Shuang-Nan; Wang, Fu-Sheng; Fu, Junliang (Frontiers in Microbiology, 2022)
Objectives: To investigate the effect and its mechanisms of different antiviral agents on the immunogenicity of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) vaccines in patients with chronic hepatitis B (CHB). Methods: A total of 125 patients with CHB receiving nucleos(t)ide analogs (NAs) monotherapy or combined with Peg-interferon-alpha (Peg-IFNα) therapy and 29 healthy controls (HCs) were enrolled. Adverse reactions (ADRs) and levels of neutralizing antibody (NAb), IgG, IgM, and peripheral cytokines post-vaccination were analyzed. Results: All ADRs were tolerable in CHB patients. Overall, no significant difference was observed in the antibody levels between patients and HCs after two doses of vaccination. An inverse correlation between NAb and IgG titers and the days after two doses was found in non-IFN group but not in IFN group. Correspondingly, peripheral interferon-γ levels were significantly higher in IFN group than in non-IFN group. After a booster dose, NAb and IgG antibodies were maintained at high levels in NA-treated patients. Conclusions: Peg-IFNα-based therapy may be beneficial for maintaining the immunogenicity of SARS-CoV-2 vaccines in CHB patients, which may be related to the high levels of IFN-γ induced by Peg-IFNα therapy. A booster dose can effectively recall the robust and long-lasting immunogenicity of SARS-CoV-2 vaccines.